81.1k views
0 votes
Find the Derivative.
f(x) = -xcos3x

User Wmac
by
4.8k points

2 Answers

2 votes

Hi there!


\large\boxed{f'(x) = -cos3x + 3xsin3x}


f(x) = -xcox3x\\\\\text{Use the product rule and chain rule to solve for the derivative:}\\\\(dy)/(dx)= -cos3x + (-x * (-sin3x) * 3)\\\\= -cos3x + 3xsin3x

User Mhelvens
by
5.0k points
5 votes

Answer:


(d)/(dx)(-xcos3x)= 3x \ sin(3x)- cos(3x)

Explanation:

Use the Product Rule for derivatives, which states that:


  • (d)/(dx) =[f(x)g(x)]= f(x)g'(x)+f'(x)g(x)

In the function we are given,
f(x)=-x \cos3x, we can break it up into two factors: -x is being multiplied by cos3x.

Now, we have the factors:


  • -x \\ $cos 3x

Before using the product rule, let's find the derivative of cos3x using the chain rule and the power rule.


  • (d)/(dx)(cos3x)= (d)/(dx) (cos3x) * (d)/(dx) (3x) \\ (d)/(dx)(cos3x)= (-sin3x) * 3 \\ (d)/(dx) (cos3x) = -3sin(3x)

Now let's apply the product rule to f(x) = -xcos3x.


  • (d)/(dx)(-xcos3x)= (-x)(-3sin3x) + (-1)(cos3x)

Simplify this equation.


  • (d)/(dx)(-xcos3x)= (x)(3sin3x) - (cos3x)

Multiply x and 3 together and remove the parentheses.


  • (d)/(dx)(-xcos3x)= 3x \ sin(3x)- cos(3x)

Therefore, this is the derivative of the function
f(x)=-xcos3x.

User Jules Ivanic
by
4.5k points